Reaction of volatiles – A crucial step in pyrolysis of coals. (15th August 2015) - Liu, Zhenyu; Guo, Xiaojin; Shi, Lei; He, Wenjing; Wu, Junfei; Liu, Qingya; Liu, Jiahe
Highlights: Volatiles formed in coal pyrolysis experience temperature increase in all reactors. Volatiles' temperature increases in coking, fluidized-bed and rotary kiln are large. Volatiles' temperature increases in fixed-bed and moving-bed reactors are small. A large volatiles' temperature increase leads to a low particulate-free tar yield. Volatiles' temperature increase promotes cracking of volatiles and coke formation. Abstract: Coal pyrolysis is regarded by many as a simple method to produce liquid fuels and chemicals and has been studied extensively in the past. However, fast coal pyrolysis technologies intended for higher tar yields and higher productivities, in comparison to the successful slow pyrolysis technologies, had common problems such as poor tar quality and plugging of the volatile products lines. The failing of many technical efforts in solving these problems calls for more fundamental studies, especially on the reaction of volatiles in major pyrolysis reactors. This is because that thermal cleavage of covalent bonds in coal that generates volatiles is a single step and depends mainly on the temperature of the coal, while the reactions of the volatiles involve multiple steps and depend on many factors especially the gas phase temperature that is generally higher than that of the coal due to the large temperature gradient in fast pyrolysis reactors. This article analyzes temperature increases in volatiles' upon their generation from coal in various pyrolysis reactors and correlates the temperature increases with tar yield and composition. Experimental results on reaction of volatiles are also presented to enlighten the importance of the volatiles' reactions.